2006
DOI: 10.1111/j.1471-0528.2006.01100.x
|View full text |Cite
|
Sign up to set email alerts
|

First‐line gemcitabine and carboplatin in advanced ovarian carcinoma: a phase II study

Abstract: Objectives To evaluate tumour response rate and toxicities of gemcitabine and carboplatin in chemonaive subjects with advanced epithelial ovarian cancer.Design A phase II study.Setting Gynaecologic oncologic unit.Population Twenty chemonaive International Federation of Gynecology and Obstetrics (FIGO) stage IIIc and stage IV subjects with ovarian cancer.Main outcome measures Tumour response, disease free and overall survival and toxicity.Methods Intravenous gemcitabine 1000 mg/m 2 on day 1 and day 8 and carbop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…However, persistence of platelet counts ≤100 × 10 9 /L frequently occurs and generally necessitates dose delays and/or reductions . Studies have demonstrated that Grades 3 and 4 thrombocytopenia occur in between 16% and 55% of patients receiving gemcitabine/platinum treatment regimens , and 3–16% of patients receiving single‐agent gemcitabine . Previous attempts to use thrombopoietin‐stimulating agents have been successful at maintaining dose intensity, although antibody formation limited the use of these agents .…”
Section: Discussionmentioning
confidence: 99%
“…However, persistence of platelet counts ≤100 × 10 9 /L frequently occurs and generally necessitates dose delays and/or reductions . Studies have demonstrated that Grades 3 and 4 thrombocytopenia occur in between 16% and 55% of patients receiving gemcitabine/platinum treatment regimens , and 3–16% of patients receiving single‐agent gemcitabine . Previous attempts to use thrombopoietin‐stimulating agents have been successful at maintaining dose intensity, although antibody formation limited the use of these agents .…”
Section: Discussionmentioning
confidence: 99%
“…145 Among them, the cisplatin or carboplatin plus paclitaxel combination has shown clinical promise for treating multiple cancers including non-small-cell lung (NSCLC), ovarian, cervical, gastric, breast and metastatic esophageal carcinomas. [179][180][181][182][183][184] Other relevant examples include cisplatin plus docetaxel and 5-FU (DNA repair targeting agent) for locally advanced head, neck and anal squamous cell carcinoma, 185,186 and carboplatin plus gemcitabine for the treatment of advanced ovarian cancer; 187,188 both combinations approved in 2006.…”
Section: Clinical Status Of Anticancer Metallodrugsmentioning
confidence: 99%
“…46 Gemcitabine, a nucleoside analogue, and carboplatin also showed significant CR. 51 Carboplatin and topotecan, which is a specific topoisomerase I inhibitor that causes single-stranded breaks in DNA during replication, showed a CR of 71%. 57…”
Section: Carboplatin As a Single Agent And Its Combinationsmentioning
confidence: 99%